Nilai Sosial Dalam Pernikahan Adat Suku Dayak Ot Danum di Kabupaten Seruyan - Regina Setiawati; Misnawati Misnawati; Lazarus Linarto; Albertus Purwaka; Isti Prihatini (Universitas Palan, 2023)
. This research aims to describe the social values ​​in the traditional marriage of the Dayak Ot Danum tribe in Seruyan Regency including: (1) material values, (2) vital values, (3) spiritual values.This research approach uses a qualitative research approach using descriptive methods. The data source used in this research is a trusted informant, namely Mr. Cilik. Data analysis This research was carried out by collecting data, identifying data, classifying data, and describing data. The results of research on social values ​​in the traditional marriage of the Dayak Ot Danum tribe in Seruyan Regency show (a) Social Value in the form of material values ​​in the traditional marriage of the Dayak Ot Danum tribe in the form of: (1) traditional traditions, (2) clothes for parents, (3) gray hair cover, (4) lapat henjan plate, (5) bahalai, (6) tantai sirau hanger, (7) sirau or lilis lamiyang, (8) engagement ring. (b) Social Values ​​in the form of vital values ​​in the traditional marriage of the Dayak Ot Danum tribe in the form of: (1) sanaman or knife, (2) dandu pangait workshop, (3) jukungsisih sahan, (4) jala penyeh balau. (c) Spiritual values ​​include truth values, beauty values, moral values ​​and religious values. The value of truth in the traditional marriage of the Dayak Ot Danum tribe is in the form of: (1) the word of God. The value of beauty in a traditional Dayak Ot Danum wedding is in the form of: (1) decoration, (2) pencak silat. The moral values ​​in the traditional Dayak Ot marriage are: (1) no trust. The religious values ​​in the traditional Ot Danum Dayak wedding are in the form of: (1) marriage blessing, (2) the Bible.